The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.dental.2015.08.149
|View full text |Cite
|
Sign up to set email alerts
|

Conversion, shrinkage, water sorption, flexural strength and modulus of re-mineralizing dental composites

Abstract: The lower surface of composite restorations should both be solid and have greater than 50% conversion. The results, therefore, suggest the experimental composite may be placed in much thicker layers than Z250 and have reduced unbounded cytotoxic monomer. Experimental materials with 10-20wt.% additionally have volumetric expansion to compensate shrinkage, antibacterial and re-mineralizing components and competitive mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 34 publications
9
76
0
1
Order By: Relevance
“…It is however demonstrated that water sorption induced volume expansion could potentially help to compensate polymerization shrinkage and relieve shrinkage stress 13) . Mass and volume increase observed with Z350 and CN were in the range of results obtained from conventional resin composites in published studies (~1 wt% and ~2 vol%) 26,35) . However, the loss of mass was observed with CN which could be due to the release of soluble species from reactive fillers.…”
Section: Mass and Volume Changessupporting
confidence: 74%
See 1 more Smart Citation
“…It is however demonstrated that water sorption induced volume expansion could potentially help to compensate polymerization shrinkage and relieve shrinkage stress 13) . Mass and volume increase observed with Z350 and CN were in the range of results obtained from conventional resin composites in published studies (~1 wt% and ~2 vol%) 26,35) . However, the loss of mass was observed with CN which could be due to the release of soluble species from reactive fillers.…”
Section: Mass and Volume Changessupporting
confidence: 74%
“…The degree of monomer conversion of polymer-based filling materials was primarily governed by chemical structure of monomers 24) , polymerization environments 25) , and thickness of the specimens 26) . High monomer conversion of resin-based restorative materials is required to ensure good physical properties and cytocompatibility of the materials 27,28) .…”
Section: Monomer Conversionmentioning
confidence: 99%
“…[182][183][184][185] Highly soluble MCPM on the surface of the composite dissolved but at the core it reacted with β-TCP to form less soluble brushite (DCP dihydrate). Partial replacement of calcium and phosphate with reinforcing opaque fillers improved the strength but these again compromised the mineral ion release and optical properties.…”
Section: Composites Containing Ttcpsmentioning
confidence: 99%
“…182 A recent study has introduced light-cured composites containing both MCPM and TCP with strength within the range expected for commercial composites. 183,184 HA precipitation at the surfaces of these composites was used to evaluate the remineralization potential of these materials. These HA layers were formed of calcium and phosphate ions released from within the composite samples.…”
Section: Composites Containing Ttcpsmentioning
confidence: 99%
“…57,61,62 Kaz1ma testinin uygulanmas1 nispeten kolayd1r ancak gerçek polimerizasyon derinliinden yüksek tahmin deerleri veren bir yöntemdir. 14,58 …”
Section: Kazima (Scrapi̇ng) Yöntemi̇unclassified